"Under the Influence of Soviet Reality": the life and work of the KGB agent "Goroshko" (Chief Bishop of the Pentecostals of the USSR Gavril Ponurko) - Korotaiev, Oleksandr (Occasional papers on religion in Eastern Europe, 2024)
The article attempts to describe, based on top secret OGPU-KGB materials, the life and work of a KGB agent, a major Pentecostal authority, chairman, and later Chief Bishop, of the All-Ukrainian (in fact, of the all-USSR) Council of Christians of the Evangelical faith, aka Pentecostals (AUCCEF), Gavril Gavrilovich Ponurko (1889-1978). The article presents interesting, previously unknown, facts from the life of Gavril Ponurko, describes his life milestones and the reasons that led Ponurko to cooperate with the special services. The article also cites the dogmatic teaching of Pentecostals in relation to the Soviet and Nazi authorities, approved by them in 1927 and 1942 at the All-Ukrainian (in fact, All-Union of SSR) congresses, which led many of them to collaborate with the Soviet, and later Nazi, special services. The "Additions" section contains photographs from the KGB archives of Gavriil Ponurko and the KGB officers who supervised his work, as well as other documents.